2005
DOI: 10.1177/0040517505056870
|View full text |Cite
|
Sign up to set email alerts
|

Electro-Mechanical Properties of Knitted Fabric Made From Conductive Multi-Filament Yarn Under Unidirectional Extension

Abstract: A theoretical model for electro-mechanical properties of intrinsically conductive knitted fabrics made from stainless steel multi-filament yarns under large uniaxial deformation is presented. The investigations are focused on the relationship between the load and electrical resistance of the fabric under uniaxial extension. A circuit network is proposed based on the loops configuration and fabric structure. The equivalent resistance of the fabric is obtained by solving the circuit equations of the network. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 16 publications
0
101
0
Order By: Relevance
“…Related research [7][8][9][10] studied the contacts between electro-conductive yarns embedded in knitted fabrics. Unlike in woven hybrid fabrics, in knitted fabrics, contacts appear between two consecutive conductive loops and not only at the intersection of weft and warp yarns.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Related research [7][8][9][10] studied the contacts between electro-conductive yarns embedded in knitted fabrics. Unlike in woven hybrid fabrics, in knitted fabrics, contacts appear between two consecutive conductive loops and not only at the intersection of weft and warp yarns.…”
Section: Methodsmentioning
confidence: 99%
“…Atalay et al [7] concluded that it is possible to manipulate the sensing properties of knitted sensors and the sensor response may be engineered by varying the production parameters applied to specific designs [8]. Zhang et al [9] created knitted strain sensors by using stainless steel and carbon yarns and identified that the contacting electrical resistance between overlapped fibers is the primary factor in the sensing mechanism. Li et al [10] also modeled the resistance of conductive knitted fabrics by superposition of the length-related resistance and contact resistance and established relationships between the resistance, tensile force, fabric length, and width.…”
Section: Introductionmentioning
confidence: 99%
“…Good flexibility and stretching property of the knitted fabrics make the sensors to fit measuring the large stretching stress and possess more extensive application range. The fabric texture, loop transfer, contact resistance and loading speed of the conductive knitted fabrics are the factors to impact the resistance of the fabrics & Zhang, 2005. These scholars studied the application of conductive knitted fabrics, and most of them aimed at the plain knitted fabrics, and few of them studied the conductive knitted fabrics with other textures, because other textures such as 1×1 rib texture has different geometric structure and electric property with the plain knitted texture.…”
Section: Abstract: Conductive Knitted Fabrics Stretching Resistancementioning
confidence: 99%
“…and the contact resistance ! [5] described according to Ohm's law [6] and Holm's contact theory [7], respectively. Many papers have described theoretical and experimental investigations of the relationship between the resistance and the elongation of conductive fabrics.…”
Section: Introductionmentioning
confidence: 99%